2020
DOI: 10.1161/strokeaha.119.027483
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Determinants of Collateral Status in Patients With Acute Ischemic Stroke in MR CLEAN Trial and Registry

Abstract: Background and Purpose— Collateral circulation status at baseline is associated with functional outcome after ischemic stroke and effect of endovascular treatment. We aimed to identify clinical and imaging determinants that are associated with collateral grade on baseline computed tomography angiography in patients with acute ischemic stroke due to an anterior circulation large vessel occlusion. Methods— Patients included in the MR CLEAN trial (Multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 49 publications
4
39
1
Order By: Relevance
“…The latter group included patients with fast or intermediate progression of infarct growth. While earlier studies have found a possible association between cervical extracranial ICA stenosis and better collateral grade during acute ACLVO stroke, 5,11 our data does not support this contention. Patients with tandem cervical ICA occlusion and intracranial ACLVO should be emergently considered for endovascular reperfusion given otherwise dismal clinical outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The latter group included patients with fast or intermediate progression of infarct growth. While earlier studies have found a possible association between cervical extracranial ICA stenosis and better collateral grade during acute ACLVO stroke, 5,11 our data does not support this contention. Patients with tandem cervical ICA occlusion and intracranial ACLVO should be emergently considered for endovascular reperfusion given otherwise dismal clinical outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Although this trend did not reach statistical significance when adjusting for other covariates, these data support earlier findings that patients with intracranial ICA occlusion are more likely to have poor collateral status and suffer worse clinical outcomes similar to fast progressors. 5,11 Slow progressors were also found to have lower rates of tandem cervical ICA occlusion relative to controls on delayed presentation. The latter group included patients with fast or intermediate progression of infarct growth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1,16 At baseline, a significant difference in collateral grade was found, with a better collateral grade in younger patients. Earlier studies noted a similar relation between collateral status and higher age, 17–19 for which the pathophysiological mechanism remains to be elucidated. We found that a significantly larger proportion of young patients with stroke directly presented at an intervention center rather than a regional primary stroke center, when compared with older patients.…”
Section: Discussionmentioning
confidence: 72%
“…All selected patients completed CTA examinations. We applied a previously reported Tan scoring system with a scale of 0–3 from the baseline CTA to assess the cerebral collateral circulation as follows: 0, absent collateral of the occluded vascular territory; 1, poor collateral filling (>0% but ≤ 50% of the occluded vascular territory); 2, moderate collateral filling (>50% but <100% of the occluded vascular territory); and 3, good collateral filling (100% of the occluded vascular territory) (Wiegers et al, 2020 ). Based on the collateral circulation scores, patients with AIS were categorized into the following two groups: GCC group with the Tan scores of 2–3 and PCC group with the Tan scores of 0–1.…”
Section: Methodsmentioning
confidence: 99%